Association between apolipoprotein B and dietary fibers - Almira Devina Gunawan; Saptawati Bardosono; Ninik Mudjihartini (Indonesian Nutrition Association, 2021)
Introduction Global awareness to the importance of natural fibers in vegetables and fruits are still generally very low. Indonesian people consume less fibers, which has been associated with the development of heart disease. Heart disease has been known as the leading cause of morbidity and mortality. Apolipoprotein B (ApoB) is a component of atherogenic particles that can be used as a marker for an increased risk of cardiovascular disease. Researches on apoB profile and its relationship with fiber intake has provided inconsistent results. This is an article review of the current literatures on the relationship between dietary fiber and serum apoB levels. Methods: This is an article review of the current literatures on the relationship between dietary fiber and apoB. We searched PubMed and Google Scholar using keyword â€œdietary fibersâ€ and â€œApoBâ€ to capture meta-analyses, observational and experimental studies. A total of 97 publication and abstracts were screened for this review. After careful screening, nine studies were finally included. Results: Two studies did not find associations between dietary fiber and serum apoB, while other seven found the association. Dietary fiber has been reported to be involved in the metabolism of serum cholesterol and blood pressure; hence, the deficiency of dietary fiber intake is believed to contribute to the epidemic of cardiovascular diseases. Several factors including nutritional status, dietary diet pattern, age, gender, physical activity, and smoking habits might influence the relationship between dietary fiber and serum apoB. Conclusion: More studies are required in the future for better understanding on the effect of dietary fiber on the apoB; hence, the risk of cardiovascular diseases.